Rancang Bangun Alat Pengukur Densitas Optik Radiograf Sinar-X Digital - Sumariyah, Sumariyah; Gunadi, Isnain; Mujib, Syaiful (BERKALA FISIKA, 2006)
A digitized X-ray radiograph’s optical density measurer has been designed.  It’s scale work is between  0.00 to  4.42. The main part of  this instrument is an optocopler sensor which will convert the light passing by  to an analog current. An optocopler circuit is a combination of LED as a light source, and a photoresistor as a light sensor. The sensor circuit is combined with a voltage devider circuit so that the voltage caused by the light and the output is work reversely. Besides, it combined with an instrumentation amplifier which amplifies the output voltage of the whole sensor. A decoder then added to the circuit to translate the BCD code to a seven segment display. The related segment, then, turned on according to the magnitude of the output voltage. The last part is a seven segment displayer which displays the measure’s result. According to a testing oxamination, the instrument is able to produce a measurement result till a resolution of 0.01.